Reformasi Birokrasi di Indonesia: Tinjauan Dari Perspektif Administrasi Publik - Mohammad Thahir Haning (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2018)
This article aimed to describe the model of bureaucratic reform that has been done, both in Indonesia, and other countries in the world. This is important to provide a comprehensive understanding of the importance of bureaucratic reform form the Public Administration perspective. The research method used in this paper was literature review obtained from various sources related to bureaucracy reform. The results of this literature review illustrates that the reform of bureaucracy ever done in some countries commonly when related to two dimensions of organizational Human Resources (HR) dimensions. Organizational dimension is related to structure, organizational culture, organizational technology, law and regulation. The HR dimension of the apparatus includes knowledge, skills, attitudes, behaviors, mindset, discipline, integrity, performance. Bureaucracy reforms conducted in various countries such as in the United States during the reign of President Bill Clinton known as reinventing government which asserts that to improve the administration of government, it is necessary to transform the values of entrepreneurship into the administration. In Europe, it is known as Neo-Weberian State (NWS) which essentially strengthens the State's role in bureaucratic service with the principle of prioritizing citizenstate relations to fulfill citizen's basic rights. Similarly, reforms are undertaken in African Commonwealth countries that emphasize the importance of bringing about transparent and accountable governments. In Indonesia, bureaucratic reform has been conducted since 1998 with aiming of producing a clean bureaucracy from corruption, collusion and nepotism (CCN). The embodiment of those objectives is stipulated through Regulation of the Minister of Administrative and Bureaucracy Reform Number 11 year 2015 regarding the road map of bureaucratic reform from 2015 to 2019. However, the implementation of these regulations has not succeeded yet in creating a professional, clean and accountable bureaucracy, and performs well.